GAMBARAN MINAT DAN PILIHAN KARIR ORANG SUNDA - Nani Nuranisah Djamal; Yulianti Yulianti (Psympathic : Jurnal Ilmiah Psikologi, 2013)
Based on the data found, interest and career choices of sundanesse are commonly less challenging. It is related to sundanesse characteristics which is based on cultural values. The purpose of this research is obtaining interest description and career choices of sundanesse by having quantitative descriptive study of 30 SMK students in east Bandung as a sample. Result shows that interest and career choices from sunda cultural background mostly shows high social interest, enterprising and conventional.